2021
DOI: 10.3390/ijerph18158062
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Soft versus Rigid Back-Support Exoskeletons during a Lifting Task

Abstract: This study investigated the influence of passive back-support exoskeletons (EXOBK) design, trunk sagittal inclination (TSI), and gender on the effectiveness of an exoskeleton to limit erector spinae muscle (ES) activation during a sagittal lifting/lowering task. Twenty-nine volunteers performed an experimental dynamic task with two exoskeletons (two different designs: soft (SUIT) and rigid (SKEL)), and without equipment (FREE). The ES activity was analyzed for eight parts of TSI, each corresponding to 25% of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 26 publications
1
11
2
Order By: Relevance
“…More importantly, the use of the Laevo induced a large increase in trunk forward flexion, from 20 deg in average without the exoskeleton to 33 deg with it. While postural changes are not systematically observed (e.g., Madinei et al (2020)), this finding is aligned with those reported by several other studies on the Laevo, in a patient transfer task (Hwang et al, 2021), in lifting tasks (Koopman et al, 2020;Schwartz et al, 2021), and in a manual assembly task (Bosch et al, 2016). Those studies consistently observed an increase in trunk forward flexion when wearing the Laevo, often around 5 deg but the magnitude varies (in some studies, the trunk inclination was loosely constrained, which might have limited the extent of the postural change).…”
Section: Effects On Kinematicssupporting
confidence: 91%
See 2 more Smart Citations
“…More importantly, the use of the Laevo induced a large increase in trunk forward flexion, from 20 deg in average without the exoskeleton to 33 deg with it. While postural changes are not systematically observed (e.g., Madinei et al (2020)), this finding is aligned with those reported by several other studies on the Laevo, in a patient transfer task (Hwang et al, 2021), in lifting tasks (Koopman et al, 2020;Schwartz et al, 2021), and in a manual assembly task (Bosch et al, 2016). Those studies consistently observed an increase in trunk forward flexion when wearing the Laevo, often around 5 deg but the magnitude varies (in some studies, the trunk inclination was loosely constrained, which might have limited the extent of the postural change).…”
Section: Effects On Kinematicssupporting
confidence: 91%
“…This should increase the hand manipulability, thereby resulting in more efficient and comfortable arm postures (Jacquier-Bret, Gorce, & Rezzoug, 2012). The fact that increased trunk flexion was observed in several other studies where the environment was less constrained suggests that it is rather the result of a choice due to the more favorable mechanical demand created by the exoskeleton, as suggested in Schwartz et al (2021) and Bosch et al (2016). However, the present study does not allow to conclude with certainty.…”
Section: Effects On Kinematicscontrasting
confidence: 55%
See 1 more Smart Citation
“…In [12] and [13], the authors compared two passive (relying on purely mechanical elements) commercially available BSEs, the BackX model AC (SuitX, Emeryville, California, USA) and the Laevo v2.56 (Laevo, Rijswijk, the Netherlands), during a series of dynamic tasks (e.g., repetitive symmetric load-lifting) and pseudostatic working postures. Similar works have been described in [14] and [15]. Studies of this type can help to guide the selection and application of passive BSE devices under diverse conditions.…”
Section: Introductionmentioning
confidence: 60%
“…Exos are used in a range of different applications, such as clinical [ 5 ] and occupational [ 6 ]. Exo research has primarily focused on device design and validation that exos reduce muscular demands, effort, or fatigue [ 7 , 8 ]. Despite the focus on exos as physical assistance devices, frequently the key barriers to societal adoption are related to comfort, fit, and freedom of movement [ 9 ].…”
Section: Introductionmentioning
confidence: 99%